Labour and the contradictory logic of logistics. (1st April 2019) - Moody, Kim
Abstract : Since the early 1980s, the way in which goods and materials are exchanged and moved has changed in what has been called the 'logistics revolution'. In the USA, the value of goods moved as freight has doubled since the late 1990s, the number of warehouses has grown by two-and-a-half times, while the amount carried by intermodal transport has grown by five times over these years. This article will argue that the system of logistics that has taken shape in the last two or three decades is deeply affected by contradictions inherent in capitalism that magnify the potential power of labour to disrupt supply chains. Among these are: the tension between the desire for the seamless movement of goods and the disruptive reality of competition and the fight for value appropriation up and down the supply chain; the push by both retailers and manufacturers for ever faster delivery of goods to market; the burden of high fixed costs that underlie the structure of contemporary logistics; and the growth of huge 'logistics clusters' concentrating tens of thousands of manual workers in important metropolitan areas. It will be argued that each of these contradictions renders the firms in these logistics networks highly vulnerable to worker actions. While such actions have been relatively rare so far, community-based pre-union organising in some major clusters, such as Chicago, is laying the basis for a future upsurge in worker organisation.